"I Just Keep My Mouth Shut": The Demobilization of Environmental Protest in Central Appalachia. (December 2019) - Lewin, Philip
This article investigates why people who take a stand against mining-related pollution sometimes abandon activism before resolving their grievances. Previous studies of this process have attributed demobilization to co-optation, violent repression, legitimation tactics, and lack of identity correspondence between movement participants and environmental justice organizations. To sharpen our understanding of why movement dissolution occurs, I investigate a case of demobilization that was not caused by these factors. Drawing on ethnographic fieldwork, in-depth interviews, and document analysis conducted in "Shale County, " a coal-producing community in Central Appalachia, I show how coal companies' subtle, yet continuous, acts of obstruction, non-cooperation, and dissimulation prompted activists to withdraw from protest. My analysis contributes to the environmental sociology and social movements literatures by (1) expanding existing theory to account for an empirical anomaly; (2) explaining the role that subtle, under-the-radar social control tactics play in suppressing environmental movements; and (3) highlighting the social conditions that render these "clandestine kicks" and "invisible elbows" effective. The model of demobilization I develop underscores the way contextual factors moderate the effectivity of industrial counter-protest tactics and foreground the active, conjuncturally specific processes through which demobilization occurs.